1992
DOI: 10.1007/bf00635616
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life during rehabilitation after coronary artery bypass surgery

Abstract: The effect of a three-phase comprehensive rehabilitation programme on the quality of life during the first postoperative year after coronary artery bypass surgery was studied in 205 male patients randomly allocated into a rehabilitation (R) and a hospital-based treatment (H) group. The rehabilitation programme included physical exercise, relaxation training, psychological group sessions, dietary advice and discussions about postoperative treatment of coronary disease. There was no difference between R and H gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 16 publications
0
20
1
Order By: Relevance
“…Significant relationships have also been observed between depression and QoL in CHD patients adding credence to the notion that depression is part of a constellation of psychological and behavioural responses to the experience of CHD [19][20][21][22]. Given the focus of cardiac rehabilitation programmes on reducing risk factors and changing health behaviour [23,24], it is surprising that depression is often unrecognised in this group [25]. Cardiac rehabilitation programmes endeavour to empower patients to improve lifestyle activities with the goal of improving QoL and reducing mortality [26][27][28].…”
Section: Depression As a Consequence Of Chdmentioning
confidence: 91%
“…Significant relationships have also been observed between depression and QoL in CHD patients adding credence to the notion that depression is part of a constellation of psychological and behavioural responses to the experience of CHD [19][20][21][22]. Given the focus of cardiac rehabilitation programmes on reducing risk factors and changing health behaviour [23,24], it is surprising that depression is often unrecognised in this group [25]. Cardiac rehabilitation programmes endeavour to empower patients to improve lifestyle activities with the goal of improving QoL and reducing mortality [26][27][28].…”
Section: Depression As a Consequence Of Chdmentioning
confidence: 91%
“…12 Several studies have documented the benefits of relaxation techniques in pre and post-operative period. In a two armed randomized controlled study, Engblom et al 13 showed increased hobby activities and reduction in scores on Beck's Depression Index during the first post-operative year after CABG in the group who had a comprehensive post-op rehabilitation (physical exercise, relaxation training, group discussion sessions and dietary advice) as compared to the group who had hospital based rehabilitation. Another study observed significant reductions in both state and trait anxiety after 6 weeks of progressive muscular relaxation in anxious patients after CABG.…”
Section: Introductionmentioning
confidence: 97%
“…Several studies have described enhanced quality of life after coronary artery bypass surgery by interpreting single item functional variables or single scores which do not fully capture the multidimensionality of the health-related quality of life concept [4][5][6]. Several studies have described enhanced quality of life after coronary artery bypass surgery by interpreting single item functional variables or single scores which do not fully capture the multidimensionality of the health-related quality of life concept [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…or subjective well-being. Several studies have described enhanced quality of life after coronary artery bypass surgery by interpreting single item functional variables or single scores which do not fully capture the multidimensionality of the health-related quality of life concept [4][5][6].…”
Section: Introductionmentioning
confidence: 99%